2014
DOI: 10.1097/qad.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of histone modifications in latently HIV-1 infected T cells

Abstract: Objectives:The transcriptional silencing of HIV type 1 (HIV-1) provirus in latently infected cells is a major hurdle on the pathway to HIV-1 elimination. The epigenetic mechanisms established by histone modifications may affect the transcriptional silencing of HIV-1 and viral latency. A systematic epigenome profiling could be applicable to develop new epigenetic diagnostic markers for detecting HIV-1 latency.Design:The HIV-1 latency cell lines (NCHA1, NCHA2 and ACH2] were compared with CD4+ T-cell line (A3.01)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Tat simultaneously decreases repressive histone methylation and increases histone acetylation at the proviral promoter. These histone modifications have been previously associated with transactivation of the HIV provirus in the promoter region [33–34]. Interestingly, we observed that EZH2 is increased in the cytoplasm after Tat treatment, which is unusual considering that EZH2 is predominantly a nuclear protein.…”
Section: Discussionsupporting
confidence: 55%
“…Tat simultaneously decreases repressive histone methylation and increases histone acetylation at the proviral promoter. These histone modifications have been previously associated with transactivation of the HIV provirus in the promoter region [33–34]. Interestingly, we observed that EZH2 is increased in the cytoplasm after Tat treatment, which is unusual considering that EZH2 is predominantly a nuclear protein.…”
Section: Discussionsupporting
confidence: 55%
“…In eukaryotes, chromatin appears to be a critical battleground for virus–host interaction. Animals use histone modifications to reinforce the latency of integrated viruses ( du Chene et al, 2007 ; Narasipura et al, 2014 ; Park et al, 2014 ). Plant DNA viruses including Geminiviruses and pararetroviruses replicate as nuclear minichromosomes or episomes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this gene has been known to be modulated by HDACis and have a role in their anti-tumor properties (24,46), it was essentially not modulated at all in the in vitro model of HIV latency in the present study (Table S1). Because its expression was elevated in the cell line models of HIV latency, it was proposed as a latency biomarker (47). Its expression in elite controllers was higher, compared with progressors and HIV seronegative individuals; CDKN1A/p21 inhibited reverse transcription of the HIV genome and transcription from the integrated provirus via inhibition of cyclin-dependent kinase 9 (CDK9), a component of P-TEFb (48).…”
Section: Secondary Mechanisms Of Action Of Hdaci and Hiv Latencymentioning
confidence: 99%